Gender Needs Analysis of Women Entrepreneurs - Ismail, Maimunah (Universiti Putra Malaysia Press, 1996)
A study was conducted on women entrepreneurs in Klang Valley to examine the characteristics and business profile of women entrepreneurs and to identify the gender needs of women entrepreneurs. The data was collected by using mailed questionnaires and 33 women entrepreneurs responded. The study revealed that 66.7% of the women were involved in retail services, 36.4% in professional services, 21.2% in manufacturing and 9.1% in wholesale. The study also showed that among the significant needs women required more exposure to entrepreneurship, business management training, system of mentoring and career counseling, networking and better access to credit facilities and better involvement in male-dominated business. Some recommendations to help develop women entrepreneurs are forth.